A comparison of economy and sagittal plane trunk movements among back-, back/front- and head-loading. Issue 9 (2nd September 2018) - Hudson, Sean; Cooke, Carlton; Davies, Simeon; West, Sacha; Gamieldien, Raeeq; Low, Chris; Lloyd, Ray
Abstract: It has been suggested that freedom of movement in the trunk could influence load carriage economy. This study aimed to compare the economy and sagittal plane trunk movements associated with three load carriage methods that constrain posture differently. Eighteen females walked at 3 km . h −1 with loads of 0, 3, 6, 9, 12, 15 and 20 kg carried on the back, back/front and head. Load carriage economy was assessed using the Extra Load Index (ELI). Change in sagittal plane trunk forward lean and trunk angle excursion from unloaded to loaded walking were assessed. Results show no difference in economy between methods ( p = .483), despite differences in the change in trunk forward lean ( p = .001) and trunk angle excursion ( p = .021) from unloaded to loaded walking. We conclude that economy is not different among the three methods of load carriage, despite significant differences in sagittal plane trunk movements. Practitioner summary: This article shows, based on mean data, that there is no difference in economy among back, back/front and head-loading, despite differences in trunk movement. It is possible a combination of factors align to influence individual economy, rather than a single set of factors, applicable to all individuals for each method.